Synthesis of one-dimensional Bi2O3–Bi5O7I heterojunctions with high interface quality. Issue 33 (26th July 2018) - Peng, Yin; Mao, Yan Ge; Liu, Ting
Abstract : One-dimensional Bi2 O3 –Bi5 O7 I heterostructures with high interface quality were first synthesized by calcining of BiOI–Bi(OHC2 O4 )·2H2 O precursors. And the obtained Bi2 O3 –Bi5 O7 I heterostructures exhibit outstanding photocatalytic activity for degrading methyl orange and phenol with high concentration. Abstract : One-dimensional Bi2 O3 –Bi5 O7 I heterostructures with enhanced visible light photocatalytic performance were synthesized by high temperature calcination of BiOI–Bi(OHC2 O4 )·2H2 O precursors. The Bi5 O7 I nanosheets uniformly grew on the Bi2 O3 porous rods. The photocatalytic performance of the obtained products was evaluated by degradation of methyl orange (MO) and phenol under visible light irradiation. The results show that the Bi2 O3 –Bi5 O7 I heterostructure displays higher photocatalytic activity than pure phase Bi2 O3 and Bi5 O7 I, and MO and phenol with high concentration can be completely degraded in 60 min under visible light irradiation using the Bi2 O3 –Bi5 O7 I (DS-2) heterostructure as a photocatalyst. This enhanced photocatalytic performance is ascribed to the synergistic effect of the suitable band alignment of Bi2 O3 and Bi5 O7 I, high interface quality and one-dimensionally ordered nanostructure. Radical scavenger experiments indicate that holes (h + ) and superoxide radicals (˙O2 − ) were the main active species for MO and phenol degradation during the photocatalytic process. This work will offer a simple route to design and synthesize junction structures with high interface quality for photocatalytic applications.